2021
DOI: 10.15294/jpii.v10i3.30695
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Biophysics with STEM Approach on Science Process Skills and Critical Thinking: Field Study on Application of NA-AOGS for Increasing Soybean Productivity and Growth Rate

Abstract: Efforts to fulfill food security to anticipate population growth in Indonesia need to be supported by universities through research and community service. The application of the Natural Animal Audio Organic Growth System (NA-AOGS) with a STEM (Science, Technology, Engineering, and Mathematics) approach is an effort to help the community increase crop yields and accelerate the growth of soybeans (Glycine max (L.) Merill). The research method used is R&D (Research & Development) which is modified from Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…In the Indonesian databases, 17 articles were published in seven of 54 Sinta STEM-related journals. Six articles (Irwanto et al, 2022;Ngabekti et al, 2019;Rokhimawan et al, 2022;Rosana et al, 2021;Rusydiyah et al, 2021;Yulianti et al, 2022) All of the 110 researchers published at most 1 article as first author. The authors in our corpus published at most two articles, either one as the first author or both as coauthors.…”
Section: Research Trajectorymentioning
confidence: 99%
See 2 more Smart Citations
“…In the Indonesian databases, 17 articles were published in seven of 54 Sinta STEM-related journals. Six articles (Irwanto et al, 2022;Ngabekti et al, 2019;Rokhimawan et al, 2022;Rosana et al, 2021;Rusydiyah et al, 2021;Yulianti et al, 2022) All of the 110 researchers published at most 1 article as first author. The authors in our corpus published at most two articles, either one as the first author or both as coauthors.…”
Section: Research Trajectorymentioning
confidence: 99%
“…Rusydiyah et al (2021) found that a PST STEM teaching internship program increased the perception and skills. STEM interventions conducting field study activities (Rosana et al,2021) through the application of NA-AOGS (natural animal audio organic growth system) technology (with soybean crops) enhances science process skills and critical thinking skills.…”
Section: Stem Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STEM approach supports student creativity by integrating knowledge, skills and abilities in solving problems (Haryadi et al, 2020). The application of the STEM-based learning process involves students directly in independent learning activities in an effort to improve human thought processes from various more advanced fields (Rosana et al, 2021). Some students use the STEMbased learning process as their best experience and want the activity time to be extended as proof that students are interested in the learning process (Özkul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The application of STEM-based learning has increased science process skills in students' knowledge (Bhakti et al, 2020;Farach et al, 2021;Khamngoen et al, 2021;Özkul et al, 2020). STEM learning that directly involves students has a positive impact so that the work they get can be utilized by many people (Rosana et al, 2021). The STEM approach is integrated to develop products, processes and systems that benefit the lives of students (Yulia, 2021).…”
mentioning
confidence: 99%